O gato doméstico (Felis catus) responde à sinais gestuais? possíveis implicações do convívio social - Melo, Silvia Beatriz Fonseca de (2008)
The cats (Felis catus) were domesticated about 9,500 years ago due to the advent of agriculture, being used to control the pests that devastated the food harvested. These animals went through an artificial selection and over generations and millennia had their behavior and morphology changed by humans. This process of domestication by man gave rise to a special ability, the understanding of human pointing gestures, clearly noticed while we feed our pets. Our goal in this study was to assess the comprehension of pointing gestures by cats and also verify the influence that social interactions exerts on the development of this ability. We found that experimental subjects from both groups, solitary animals and social animals, were able to follow human indication in order to find hidden food. However, social interaction had no effect on cats performances. The ability tested here probably evolved during the process of domestication of this species, and social interaction seems to exert little or no influence upon its expression